2017
DOI: 10.1155/2017/4793465
|View full text |Cite
|
Sign up to set email alerts
|

Response Detection of Castrate-Resistant Prostate Cancer to Clinically Utilised and Novel Treatments by Monitoring Phospholipid Metabolism

Abstract: Androgen receptor (AR) activation is the primary driving factor in prostate cancer which is initially responsive to castration but then becomes resistant (castration-resistant prostate cancer (CRPC)). CRPC cells still retain the functioning AR which can be targeted by other therapies. A recent promising development is the use of inhibitors (Epi-1) of protein-protein interaction to inhibit AR-activated signalling. Translating novel therapies into the clinic requires sensitive early response indicators. Here pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…A 31 P NMR study of LNCaP cells indicated a high NAD level relative to nucleoside triphosphates. 56 At the same time the inhibition of LDH activity may come from higher NAD, as this inhibition is caused by a ternary LDH-NAD-pyruvate complex and thus is determined by a combination of high NAD and pyruvate levels. It has also been concluded from metabolic control theory that the control of the 13 C label exchange between pyruvate and lactate in EL4 cells is shared by membrane MCT and LDH activity.…”
Section: Discussionmentioning
confidence: 99%
“…A 31 P NMR study of LNCaP cells indicated a high NAD level relative to nucleoside triphosphates. 56 At the same time the inhibition of LDH activity may come from higher NAD, as this inhibition is caused by a ternary LDH-NAD-pyruvate complex and thus is determined by a combination of high NAD and pyruvate levels. It has also been concluded from metabolic control theory that the control of the 13 C label exchange between pyruvate and lactate in EL4 cells is shared by membrane MCT and LDH activity.…”
Section: Discussionmentioning
confidence: 99%